Adaptive traffic distributing based on dynamic topology for multipath routing in MANET - AN Hui-yao1; LU Xi-cheng2; PENG Wei2; PENG YU-hang2 (Tongxin xuebao)
In order to circumvent these problems that led to impose both communications overhead on the network and processing overhead on node in most MANET multipath routing schemes proposed so far when the same size load was distributed into the various paths regardless of the qualities, a scheme called adaptive dynamic traffic distributing multi- path routing（ADTDMRP）was proposed, which distributed by proportioning flows among multiple paths dynamically based on the weight value of each path. It made routing decisions using only “local” information at the most of time and thus re- ducing the network overhead. By implementing the algorithm on the OPNET modeler, the results demonstrate that adaptive dynamic traffic distributing multipath routing is indeed a viable alternative to MANET routing approach.